Improvement Of Feed Utilization And Survival Rate Of Clarias Gariepinus Using Probiotic And Fermented Feed In Cemorokandang District - Muhammad Fakhri; Arning Wilujeng Ekawati (Journal of Innovation and Applied Technology, 2019)
The common problem faced by catfish culturing in Cemorokandang District is high feed costs, low survival rate and high feed conversion ratio. The purpose of this acivity was to solve the problems faced by the farmers of catfish culture. The method of this activity was to transfer a knowledge and appropriate technology to farmers through Participatory Rural Appraisal and Participatory Technology Development. The activities that have been carried out in catfish culture are: (1) socialization, training and mentoring of probiotic production, (2) socialization, training and mentoring of fermented feed production using soy flour and wheat bran (3) construction of 2 m diameter of tarpaulin tanks , (4) provision of catfish seeds 7 cm, (5) the application of fermented feed and probiotic, and (6) monitoring and evaluation.